Uwarunkowania wzrostu konkurencyjności produkcji żywca wieprzowego w Polsce - Szymańska, Elżbieta (Conditions of Competitiveness Increase of Pig Production in Poland, 2006)
The aim of the study is to estimate the most important conditions of competitiveness increase in Poland. Research shows that competitiveness on the world pork market is getting stronger. To cope with it Polish producers have to enlarge concentration of herds and the scale of production. An essential condition is a reduction of production costs and also improvement of pig meat quality.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 405-410